Stigmastane-type steroids with unique conjugated Δ7, 9(11) diene and highly oxygenated side chains from the twigs of Vernonia amygdalina. (February 2019) - Liu, Xiangzhong; Tian, Wenjing; Wang, Guanghui; Xu, Qiannan; Zhou, Mi; Gao, Shuo; Qiu, Daren; Jiang, Xin; Sun, Cuiling; Ding, Rong; Lin, Ting; Chen, Haifeng
Abstract: Veramyosides A-J, eleven undescribed stigmastane-type steroids, including one aglycone and ten glycosides, along with three known homologues were isolated from the twigs of Vernonia amygdalina Delile (compositae). All compounds featured a stigmastane-type steroid skeleton with a unique conjugated Δ 7, 9(11) diene segment and highly oxygenated side chains with a γ -lactone or an α, β -unsaturated five-membered lactone ring. The structures of veramyosides A-J and their absolute configurations were unambiguously elucidated by HR-ESI-MS, extensive NMR spectroscopy, in situ dimolybdenum CD methods, modified Mosher's method, quantum chemical calculation of their ECD curves, and CD comparison methods on basis of their biogenetic pathway. In addition, all isolates were investigated for their effects on RXRα transcription, and their effects on the NF-κB signaling pathway were also evaluated. Graphical abstract: Veramyosides A-J, eleven undescribed stigmastane-type steroids, were isolated from the twigs of Vernonia amygdalina Delile (compositae). All compounds were evaluated for their effects on RXRα transcription and NF-κB signaling pathway. Highlights: Compounds featured a steroid skeleton with a unique conjugated diene Δ 7, 9(11) segment. The stereochemistry of compounds was elucidated by derivative reaction and quantum chemistry. The preliminary structure activity relationship of the Δ 7, 9(11) stigmastane-type steroids was discussed.